Trust in public health policy in the time of the COVID-19 epidemic in Israel - Jochanan Benbassat (BMC, 2024)
Abstract The government of Israel provides universal health care through four health care organizations ("sick funds") that enjoy general public trust. In hindsight, the response of the government to the COVID-19 epidemic seems reasonable. In the first year of the epidemic, tests and vaccines were developed and other measures were taken, including social distancing, focusing on risk factors for infection and disease severity, and improving treatment. The COVID-19 mortality rate between January 2000 and June 2021 was around 750 per million inhabitants, well below the OECD average of 1300. Still, although the control measures were largely well received, the media and an ad hoc non-governmental Emergency Council for the coronavirus crisis in Israel criticized the government's response to the epidemic thereby contributing to a decline in public trust in government policy. This commentary provides an overview of the importance of trust in medical institutions and the difficulties of evaluating healthcare decisions in an attempt to justify three conclusions. First, when physicians and self-appointed experts publicly disapprove of a government policy, they should consider the trade-off between improving care and undermining public trust. Second, when evaluating a medical decision, experts should not ask, "Would I have acted differently?" but rather, "Was the decision under review completely unreasonable?" Thirdly, criticism is certainly worth listening to. However, I believe that by calling for organized resistance against the government, the publicly announced establishment of the Emergency Council for the Corona crisis blatantly crossed the line between constructive criticism and destructive mistrust.